Patency of Litomosoides sigmodontis infection depends on Toll‐like receptor 4 whereas Toll‐like receptor 2 signalling influences filarial‐specific CD4+ T‐cell responses. Issue 4 (April 2016) - Rodrigo, Maria B.; Schulz, Sandy; Krupp, Vanessa; Ritter, Manuel; Wiszniewsky, Katharina; Arndts, Kathrin; Tamadaho, Ruth S. E.; Endl, Elmar; Hoerauf, Achim; Layland, Laura E.
Summary: BALB/c mice develop a patent state [release of microfilariae (Mf), the transmission life‐stage, into the periphery] when exposed to the rodent filariae Litomosoides sigmodontis . Interestingly, only a portion of the infected mice become patent, which reflects the situation in human individuals infected with Wuchereria bancrofti . Since those individuals had differing filarial‐specific profiles, this study compared differences in immune responses between Mf + and Mf – infected BALB/c mice. We demonstrate that cultures of total spleen or mediastinal lymph node cells from Mf + mice produce significantly more interleukin‐5 (IL‐5) to filarial antigens but equal levels of IL‐10 when compared with Mf – mice. However, isolated CD4 + T cells from Mf + mice produced significantly higher amounts of all measured cytokines, including IL‐10, when compared with CD4 + T‐cell responses from Mf – mice. Since adaptive immune responses are influenced by triggering the innate immune system we further studied the immune profiles and parasitology in infected Toll‐like receptor‐2‐deficient (TLR2 −/− ) and TLR4 −/− BALB/c mice. Ninety‐three per cent of L. sigmodontis ‐exposed TLR4 −/− BALB/c mice became patent (Mf + ) although worm numbers remained comparable to those in Mf + wild‐type controls. Lack of TLR2 had no influence on patency outcome or worm burden but infected Mf + mice had significantly lower numbers of Foxp3 + regulatory T cells and dampened peripheral immune responses. Interestingly, in vitro culturing of CD4 + T cells from infected wild‐type mice with granulocyte–macrophage colony‐stimulating factor‐derived TLR2 −/− dendritic cells resulted in an overall diminished cytokine profile to filarial antigens. Hence, triggering TLR4 or TLR2 during chronic filarial infection has a significant impact on patency and efficient CD4 + T‐cell responses, respectively.